British Thoracic Society guideline for the use of long-term macrolides in adults with respiratory disease. Issue 1 (23rd April 2020) - Smith, David; Du Rand, Ingrid A; Addy, Charlotte; Collyns, Timothy; Hart, Simon; Mitchelmore, Philip; Rahman, Najib; Saggu, Ravijyot
Abstract : The full British Thoracic Society (BTS) guideline for the use of long-term macrolides in adults with respiratory disease is published in Thorax. The following is a summary of the recommendations and good practice points. The sections referred to in the summary refer to the full guideline. The appendices are available in the full guideline and online appendices are available on the BTS website. This is the first BTS guideline to use the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach as part of the process of guideline development and the guideline was used to pilot the new methodology.